Effect of Grape Seed Extract on the Physicochemical and Sensory Properties of Chicken Nuggets - Kaur, Simranjeet; Kumar, Sunil; Bhat, Z.F. (Journal of Meat Science, 2015)
The present study was designed to evaluate the possibility of utilization of grape seed extract in the development of designer chicken nuggets. The products were developed by incorporating different levels of grape seed extract (0.1%, 0.2%, and 0.3%) and were analyzed for various physicochemical and sensory parameters. A significant (p
Keywords: Grape Seed Extract; Physicochemical; Sensory Properties; Chicken Nuggets